Sexual Behaviours of Sexual Minorities in Surkhet of Nepal: Risk and Safety - Yogi, Belpatra Nath (KMC Journal, 2023)
The article analyzes sexual behaviours at risk and safety against the risk among the sexual minorities in Surkhet district of Nepal. It is a cross-sectional descriptive study based on quantitative data. One hundred thirteen sexual minorities selected through snowball sampling were interviewed. The data were analyzed using simple statistical tools such as number, percent and mean - nearly two-thirds of sexual minorities were involved in sexual activity before their maturation at the age below 20. Most (84.1%) of them had multiple sexual partners, and all had an active sex life preferring anal and oral sex the most. Many have put their sexual behaviours at risk through their sexual involvement with drug users and commercial motives in sex. However, they have adopted a few measures of safety to prevent them from sexually transmitted infections and other worsening health conditions. Above three-quarters of them used condoms while indulging in anal sex and vaginal sex with their sex partners. One-fifth of them visited health institutions for general health check up, and nearly half of them tested for HIV and STDs. Despite their efforts to adopt health safety by many of them, a large proportion of the sexual minorities have been exposed to risky sexual behaviours, making them more vulnerable to diseases and poor health. So, a joint effort from governmental, non-governmental, and public sectors is urgently required to minimize the risks from their sexual behaviours and accelerate the safety against the risks.